Potential Marine Ecotourism Development Poncan Island Tower Sibolga in North Sumatra Province - Adawiyah, Rabiatul; Yosswaty, Dessy; ', Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractByRabiatul Adawiyah 1), Dessy Yosswaty dan Efriyeldi 2)The research was conducted on the Moon from October-November 2014 of Poncan Island Tower Sibolga in North Sumatra Province. Order to determine the potential for marine ecotourism of Poncan Island Tower to serve as a marine tourism area. The method used in this study is a survey method, ie by observing, collecting data and samples directly into the field and collect the necessary data qualitatively and quantitatively. Data were taken and observed consist of primary data and secondary data. The results showed that the potential of the object and appeal Poncan Island ecologically Tower is yellowish white sand with crystal clear waters and coral reefs which have magnificent beauty, as well as activities that can be done such as: fishing, snorkeling and enjoy activities such as driving around the island . The calculation of the potential economic value obtained is Rp. 16.614.713.500 billion. This suggests that the Pulai Poncan Tower decent and has a fascination for visitors to come.Keywords: Marine Ecotourism, Development, Poncan Island Tower